2014
DOI: 10.1371/journal.pone.0085670
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Fishing and Marine Biodiversity Changes Using Fishers' Perceptions: The Spanish Mediterranean and Gulf of Cadiz Case Study

Abstract: BackgroundThe expansion of fishing activities has intensively transformed marine ecosystems worldwide. However, available time series do not frequently cover historical periods.MethodologyFishers' perceptions were used to complement data and characterise changes in fishing activity and exploited ecosystems in the Spanish Mediterranean Sea and Gulf of Cadiz. Fishers' interviews were conducted in 27 fishing harbours of the area, and included 64 fishers from ages between 20 to >70 years old to capture the experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 52 publications
3
61
0
Order By: Relevance
“…However, the pure effect of spatial variables on biodiversity metrics of most marine groups was small in deviance partitioning analyses, suggesting that a large fraction of their influence was related to the spatial structure of environmental and human variables considered. Although not conclusive, the remaining portion of their influence might reflect the role played by environmental or human variables not considered in the present study or past events (Legendre and Legendre, 1998), such as uneven historic human pressures, for example fishing activity in the coastal areas of the Mediterranean Sea (Azzurro et al, 2011;Coll et al, 2014).…”
Section: Discussionmentioning
confidence: 84%
“…However, the pure effect of spatial variables on biodiversity metrics of most marine groups was small in deviance partitioning analyses, suggesting that a large fraction of their influence was related to the spatial structure of environmental and human variables considered. Although not conclusive, the remaining portion of their influence might reflect the role played by environmental or human variables not considered in the present study or past events (Legendre and Legendre, 1998), such as uneven historic human pressures, for example fishing activity in the coastal areas of the Mediterranean Sea (Azzurro et al, 2011;Coll et al, 2014).…”
Section: Discussionmentioning
confidence: 84%
“…spiny dogfish in the Western Scotian Shelf; Araújo & Bundy 2012), or the expansion of fisheries to deeper areas. The latter may be the case in the Mediterranean ecosystems (Coll et al 2014).…”
Section: Relating Trophic Level-based Indicators To Fishingmentioning
confidence: 92%
“…divergence of TL-related descriptors at high trophic levels; Van der Lingen & Miller 2011) although they also may be well correlated (e.g. Coll et al 2014). These discrepancies or similarities in TL estimations warrant further examination and refinement of both isotope studies (e.g.…”
Section: Implications Of Estimating Tls Using Different Methodsmentioning
confidence: 98%
“…The species is very popular for human consumption in the Mediterranean Sea (Capapé et al 2008), and it is a common fisheries by-catch in the eastern North Atlantic being the main shark species captured in northern Spain and northern France (Cavanagh 2005). Although populations have generally either remained stable or even increased over the last few decades (Jukic-Peladic et al 2001; UNEP-MAP-RAC/SPA 2013; Coll et al 2014;McHugh et al 2011), declines in lesser spotted dogfish landings have been reported for the Aegean Sea (Damalas and Vasilopolou, 2011), the Adriatic Sea (Barrausse et al, 2014) and the Tyrrhenian Sea (Ferretti et al 2005).…”
Section: Introductionmentioning
confidence: 99%